Unconventional Determinants of Greenhouse Gas Emissions: The role of trust. (25th August 2015) - Carattini, Stefano; Baranzini, Andrea; Roca, Jordi; Petit, Olivier; Özkaynak, Begüm; Ring, Irene
Abstract Social norms have been included in the theory of collective action to overcome difficulties in explaining why commons may perform better when self‐regulated. The role of trust has been identified in several contexts of local social dilemmas, but only recently has been extended to global commons, based on large descriptive evidence collected by Elinor Ostrom. However, no quantitative evidence was available until now. Using a dataset of 29 European countries over the period 1990–2007, we provide empirical evidence in favour of the role of trust in global dilemmas. We find a non‐negligible impact of trust on greenhouse gas emissions, which can support Ostrom's intuition on the social roots of pro‐environmental behaviour. Copyright © 2015 John Wiley & Sons, Ltd and ERP Environment